A study protocol for an ongoing multi-arm, randomized, double-blind, sham-controlled clinical trial with digital features, using portable transcranial electrical stimulation and internet-based behavioral therapy for major depression disorders: The PSYLECT study. (3rd June 2022) - Borrione, Lucas; Cirillo, Patricia C; Aparicio, Luana VM; Cavendish, Beatriz A; Valiengo, Leandro; Moura, Darin O; de Souza, Juliana P; Luethi, Matthias S; Klein, Izio; Bariani, Bruna; Gallucci-Neto, José; Suen, Paulo; et al.
ABSTRACT: Background: Transcranial electrical stimulation (tES) is considered effective and safe for depression, albeit modestly, and prone to logistical burdens when performed in external facilities. Investigation of portable tES (ptES), and potentiation of ptES with remote psychological interventions have shown positive, but preliminary, results. Research design: We report the rationale and design of an ongoing multi-arm, randomized, double-blind, sham-controlled clinical trial with digital features, using ptES and internet-based behavioral therapy (iBT) for major depressive disorder (MDD) (NCT04889976). Methods: We will evaluate the efficacy, safety, tolerability and usability of (1) active ptES + active iBT ('double-active'), (2) active ptES + sham iBT ('ptES-only'), and (3) sham ptES + sham iBT ('double-sham'), in adults with MDD, with a Hamilton Depression Rating Scale – 17 item version (HDRS-17) score ≥ 17 at baseline, during 6 weeks. Antidepressants are allowed in stable doses during the trial. Results: We primarily co-hypothesize changes in HDRS-17 will be greater in (1) 'double-active' compared to 'ptES-only, ' (2) 'double-active' compared to 'double-sham, ' and (3) 'ptES-only' compared to 'double-sham.' We aim to enroll 210 patients (70 per arm). Conclusions: Our results should offer new insights regarding the efficacy and scalability of combined ptES and iBT for MDD, in digital mental health.